Imagens da libertação: a atuação política da Igreja Católica de Nova Iguaçu por meio do jornal A Folha (1974-1981) - Nascimento, Rafael Cerqueira do (2007)
This research analyses the political role played by the Catholic Church in Nova Iguaçu, essentially by its newspaper A Folha, from 1974 to 1981. Establishes the Catholic Church of Nova Iguaçu as part of the political opposition to the regime during the second half of 1970 decade. Evaluates this catholic weekly publication as an example of the alternative press during this period, observed as a political phenomenon of its epoch, of searching for political resistance fields inside Brazilian society during the military regime. Therefore, considering changes in Church, mainly after the rising of Liberation Theology, this study verifies the contribution of A Folha to the building of a catholic imaginary, which defines the social liberation identity assumed by some groups inside the institution. Thus, the study identifies the criticism addressed by the Catholic Church of Nova Iguaçu to capitalist society and the Brazilian military regime, and also analyses how the struggle for social justice became source of political participation of groups inside the Church, clarifying the use of religious discourse to establish a conflict at level of social representation.